Development and application of a Monte Carlo virtual detector—A novel nuclear pulse signal generator. (1st December 2021) - Sangang, Li; Yi, Cheng; Li, Yang; Lei, Wang; Mingzhe, Liu
Highlights: A Monte Carlo virtual detector based on the Geant4 simulation and FPGA was designed. The Monte Carlo virtual detector allows the detector and the radioactive source parameters to be set, e.g., detector material and energy of the radioactive source. The output nuclear pulse signals have the physical significance of reflecting all kinds of interaction between the ray and the matters in real detector. Abstract: The generation of real nuclear pulse signals need a detector and a radiation source. In order to replace some expensive detectors or harmful radiation sources, and precisely evaluate a nuclear detection system, a monte Carlo virtual detector (MCVD) which could simulate different types of detectors and radiation sources was designed to generate nuclear pulse signals. The generated nuclear pulse signals were verified in amplitudes and time intervals, and were applied to test the performance of a multi-channel pulse amplitude analyzer. The results showed that the amplitudes were proportional to the corresponding energies, the time intervals between two consecutive pulses obeyed an exponential distribution, and the generated energy spectrum not only included the amplitude information of the full-energy peak, but also included the amplitude information of the Compton plateau and backscatter peak (scattered signals), etc. Thus, the generated nuclear pulse signals have the physical significance of reflecting all kinds of interaction between the ray and the matters in real detector, and can more precisely evaluate nuclear detection systems.